Spatial Characteristics of Porang Development and Competitive Advantages in The Central Lombok Highlands - Baiq Santi Rengganis; Baiq Diah Fitasari; Slamet Mardiyanto Rahayu (Jurnal Penelitian Pendidikan IPA, 2023)
: In 2020 Indonesia's export volume for porang reached 14,568 tons compared to 2019 of 11,720, so it deserves priority for development including in Central Lombok Regency. This study aims to analyze the spatial characteristics of porang development, analyze the competitiveness of porang, and analyze the stabilization of porang production in Central Lombok Regency. Data analysis uses the analysis of Localization Coefficient, Specialization Coefficient, Location Quotient (LQ), Basic Service Ratio (BSR), Regional Multiplier (RM), and competitive profit. To obtain diversity and variety of data, Central Lombok is divided into 4 research areas or clusters; Batu Keliang District Area, Kopang District Area, Pujut District Area, Praya Barat District Area. Furthermore, in each cluster area, 5 samples (respondents) were determined for each commodity under review (porang, cassava, sweet potato). Thus the number of respondents to 60 people. While secondary data is in the form of time series data collected from 2019 to 2021, including data on the development of harvested area, production and productivity of porang